Skin and Soft Tissue Infections: Bacteriological Profile and Antibiotic Resistance Pattern of Isolates - Sah, P; Khanal, R; Upadhaya, S (Journal of Universal College of Medical Sciences, 2013)
INTRODUCTION: Emergence and spread of antibiotic resistance in organisms causing skin and soft tissue infections (SSTIs) is posing a great therapeutic challenge. This study aimed to determine bacteriology of SSTIs and study antibiotic resistance among the isolates. MATERIAL AND METHODS: A retrospective analysis of 149 consecutive pus specimens received at microbiology laboratory of Universal College of Medical Sciences & Teaching Hospital, Bhairahawa over a period of 8 months from July 2012 to February 2013 was done. The bacterial isolates were identified by standard microbiological techniques and antibiotic susceptibility testing was done by Modified Kirby-Bauer method. RESULTS: Growth was seen in 92 (62%) specimens out of which 88 specimens yielded single isolate and 4 specimens yielded 2 isolates. Hence a total of 96 isolates were isolated. The commonest isolates were Staphylococcus aureus (n=39) followed by E. coli (n=11), Pseudomonas spp (n=11), Coagulase negative staphylococci (n=9), Klebsiella spp (n=6), Proteus spp (n=5), Streptococcus spp (n=4), Acinetobacter spp (n=1), and unidentified gram negative bacilli (n=10). Among gram positive cocci susceptibility to Amikacin was highest followed by vancomycin and gentamycin. Among gram negative bacilli aminoglycosides and ciprofloxacin susceptibility was high, however all E. coli isolates were ciprofloxacin resistant. Majority of isolates were resistant to amoxicillin, ceftriaxone and cotrimoxazole. CONCLUSION: In conclusion this study reports the commonest organism in SSTIs is S. aureus followed by E.coli and Pseudomonas spp. Continued monitoring of susceptibility pattern need to be carried out to detect the true burden of antibiotic resistance in organisms and prevent their further emergence by judicious use of drugs. DOI: http://dx.doi.org/10.3126/jucms.v1i3.8759 Journal of Universal College of Medical Sciences Vol.1(3) 2013: 18-21